The use of client-engaged specialists to support opportunistic estimates: evidence from the insurance industry - Ege, Matthew S.; Imdieke, Andrew J.; Stuber, Sarah B. (Review of Accounting Studies, 2025)
We use unique disclosures in the insurance industry to examine whether client-engaged specialists (i.e., external actuaries) affect opportunism within the claim loss reserve. Using a fixed-effects approach, we find that external actuaries significantly affect the opportunism in the claim loss reserve, approaching half the effect of the auditor. With respect to actuary characteristics, we find a positive (negative) association between actuary permissiveness (actuary size) and opportunism in the claim loss reserve. In additional analyses, we find that the relation between actuary permissiveness and claim loss reserve opportunism is stronger when insurers have incentives to opportunistically manage the claim loss reserve. This relation continues to persist in the presence of high-quality auditors. Overall, we provide evidence suggesting that client-engaged external actuaries can be used to support opportunistic claim loss reserve estimates.